2016
DOI: 10.1111/tmi.12774
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review: strategies of providing care for children with chronic health conditions in low‐ and middle‐income countries

Abstract: Abstractobjectives To identify and review strategies of providing care for children living with chronic health conditions in low-and middle-income countries.methods We searched MEDLINE and Cochrane EPOC databases for papers evaluating strategies of providing care for children with chronic health conditions in low-or middle-income countries. Data were systematically extracted using a standardised data charting form, and analysed according to Arksey and O'Malley's 'descriptive analytical method' for scoping revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 89 publications
(213 reference statements)
0
11
0
Order By: Relevance
“…CHECK offers a model for how to merge social and health services in order to obtain improved care for these children. While children everywhere would benefit from comprehensive well-coordinated care, the CHECK model may be premature for low- and middle-income countries where access to basic health care is the first priority (Graham et al, 2016). Also, implementation of a model such as CHECK may not be necessary in countries where strong connections already exist between health-care and social service systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHECK offers a model for how to merge social and health services in order to obtain improved care for these children. While children everywhere would benefit from comprehensive well-coordinated care, the CHECK model may be premature for low- and middle-income countries where access to basic health care is the first priority (Graham et al, 2016). Also, implementation of a model such as CHECK may not be necessary in countries where strong connections already exist between health-care and social service systems.…”
Section: Resultsmentioning
confidence: 99%
“…Children with medical complexity (CMC) represent a growing and crucial group of children with unique medical needs that can be difficult to serve and have a tremendous impact on the health-care system around the world (Cohen et al, 2012; Graham et al, 2016; Judson, 2004). Although the definition varies in the literature, CMC have one or more chronic, severe health conditions, extensive health service needs, often have functional limitations, and have high utilization of health-care resources (Berry et al, 2013; Cohen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A previous review by Graham et al which included studies published through 2015 on the same topic area—strategies for chronic care for children in LMICs found results similar to ours—strong evidence for patient, family, and community education and involvement; integration of community resources and psychosocial support; and emphasised the importance of health system inputs including health worker training, infrastructure and information systems. 14 Further, they noted the dearth of evidence on comprehensive models of care and any in the literature were limited to HIV models of care. Our review shows limited progress in increasing the number of these evaluations and expanding the diversity of conditions addressed with just 16 studies of models of care identified, a large majority of which again focused on HIV.…”
Section: Discussionmentioning
confidence: 99%
“…We limited studies to manuscripts published after 1 January 2015 to build off a previous review of the same scope. 14 We did not set language limits. One reviewer (LKR) conducted the primary search, the external expert group guided the selection of references that were comprehensive and relevant to the scope of this review and solved any disagreements by consensus, and all authors approved of the final selection of references.…”
Section: Methodsmentioning
confidence: 99%
“…However, several issues need to be highlighted. Providing such paediatric and child health services requires a system-approach with integrated models of care spanning healthcare organizations, communities, patients, and sometimes other stakeholders [ 62 ]. For example, long-term disability requires sustained interactions with the medical and rehabilitative services [ 4 , 50 , 63 ].…”
Section: Discussionmentioning
confidence: 99%